Stiction-model-based re-tuning of PI controller for industrial process control loops - Masaharu Daiguji; Yoshiyuki Yamashita (SICE Journal of Control, Measurement, and System Integration)
Control valve stiction is prevalent in the process industry, leading to oscillations in process variables and degrading unit performance. Stiction is usually repaired during scheduled plant maintenance, but until then, compensation methods are required to reduce oscillations. This study presents a novel approach to address this problem by identifying control valve and process models and optimizing control parameters. The method combines a stiction model, a process model, and a controller to achieve optimal control with stiction. Additionally, the method incorporates a controller output filter and considers undershooting during the step response for control performance assessment. The proposed method is designed to handle different types of valve stiction models, providing a versatile solution. The results show that our method significantly improves the control loop performance of all valves tested.